Characterizing Usage Patterns for Powered Two-Wheelers from Automatic Vehicle Identification Data in Melbourne, Australia. Issue 1 (January 2014) - Delbosc, Alexa; Rose, Geoffrey
Australia's cities face increasing concerns about traffic congestion and pollution, concerns that encourage an interest in sustainable transport choices. Most of the focus of these concerns has been on cars, public transport, and active transport, whereas the role of powered two-wheelers (PTWs)–-specifically, motorcycles and motor scooters–-has received little attention. Most PTW research focuses on road safety implications, and little is known about their usage patterns. Automatic vehicle identification counts at two major tolled freeways in Melbourne, Victoria, Australia–-one radial freeway close to the city center and one orbital freeway 20 to 30 km southeast of the city center–-were analyzed. Automatic vehicle classification equipment recorded hourly traffic counts and PTW counts from 2006 to 2012. The classified count data were analyzed to explore the pattern of PTW use by time of day, by day of week, and across the seasons. Regression analyses were used to examine weather effects. Comparisons were drawn between PTW and non-PTW traffic and between the radial and orbital freeways. A discussion of the findings and suggestions for additional research are presented.